Health literacy among older adults in Switzerland: cross-sectional evidence from a nationally representative population-based observational study (Swiss Medical Weekly, 2022)
BACKGROUND AND AIM: Despite being widely regarded as a major cause of health inequalities, little is known regarding health literacy and its association with certain personal characteristics among older adults in Switzerland. To fill this gap, this study assesses health literacy and its associations with individuals’ social, regional, and health characteristics in a nationally representative sample of adults aged 58 years and older in Switzerland.METHOD: We use data of 1,625 respondents from a paper-and-pencil self-completion questionnaire (cooperation rate: 94.3%) that was administered as part of wave 8 (2019/2020) of the Survey of Health, Ageing and Retirement in Europe (SHARE) in Switzerland. Health literacy is measured using the short version of the European Health Literacy Survey questionnaire (HLS-EU-Q16). The scale includes 16 items whose dichotomised responses allow the construction of different indices and sub-indices aimed at measuring various aspects of health literacy. We use multivariable regressions to explore how respondents' sociodemographic characteristics are independently associated with health literacy.RESULTS: Overall, 6.8% of the respondents had inadequate health literacy, 24.6% problematic health literacy, and 68.6% sufficient health literacy. There were significant associations between health literacy and individuals' gender, education, economic situation, and self-rated health. Women had higher levels of health literacy than men (p